Diagnostic Interview for Genetic Studies: validity and reliability of the Croatian version. (February 2017) - Kralj, Žana; Dedić, Milenka; Kovačević, Anđela; Malički, Mario; Dedić, Jelena; Pelivan, Marina; Vuković, Dubravka; Fisher, Carrie; Kember, Rachel L.; Nurnberger, John; Bućan, Maja; Britvić, Dolores
Abstract : Objective: To test the validity and reliability of the Diagnostic Interview for Genetic Studies (DIGS) in patients with mental illness in Croatia. Materials and methods: Following translation, back-translation, and pilot testing, the Croatian version of DIGS (CRO-DIGS) was administered to a total of 150 inpatients and outpatients diagnosed at the Clinical Hospital in Split with bipolar and major depressive disorder ( n =56), schizophrenia and schizoaffective disorder ( n =62), and alcohol dependence or use disorders ( n =32). Initial testing was performed independently by one interviewer and one observer blinded to the diagnosis, and a retest was performed after 8 weeks by a third examiner. Results: The validity of CRO-DIGS was high ( κ =0.916), with an excellent inter-rater ( κ =0.824) reliability, especially for bipolar disorder ( κ =0.956). Following an 8 week test–retest interval, the reliability for all diagnoses was found to be excellent ( κ =0.843). Conclusion: Our study has shown excellent validity and reliability of the Croatian version of DIGS, making it a promising instrument to assess mental illness of patients. The development of a valid and reliable diagnostic tool such as the CRO-DIGS will considerably advance the scientific communities' ability to carry out genetic studies of psychiatric illness in the region.